Why companies practice corporate social responsibility - POPE, Shawn (Institutional Knowledge at Singapore Management University, 2022)
The article discussed why companies practice corporate social responsibility (CSR) and their meta-analysis of 200 surveys over 20 years found that CSR is often embraced as a “halo” strategy.